Identification Of Dry Eye Syndrome Risk Factors In Workers Who Use Visual Display Terminals (VDT) - Rahardjo, Abdi Malik; Ramdhany, Fikri Krisda; Putrinahrisyah, Muthia; Widyawati, Eva Zerlina; Khaulah, Mauhibah; Tunjungsari, Feny; Sumarauw, Pamela Andria Putri Kusuma (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2024)
Dry eye syndrome is a multifactorial disease of the eye air and eye surface which causes symptoms of discomfort, visual disturbances, and instability of the eye air layer which has the potential to damage the eye surface. This condition has an impact on productivity, activities in the work environment, apart from that it also has an impact on lower employment opportunities, decreased working hours and increases a person's inability to work. Using visual display terminals for 5-7 hours/day can significantly increase the incidence of dry eye syndrome. Therefore, paying attention to the risk factors of visual display terminal workers is very important in preventing the occurrence of dry eye syndrome. The research method uses literature studies from several national and international journals obtained from 18 reference sources through searches on PubMed and Google Scholar published in the last 5 years. There were 18 articles with full text that met the inclusion criteria and contained several risk factors associated with the incidence of dry eye syndrome. Risk factors for dry eye syndrome in workers who use visual display terminals include age, gender, screen exposure time, psychological stress, work environment, use of contact lenses, use of drugs and history of surgery, refractive disorders, and length of work. Identification of risk factors for dry eye syndrome in workers who use visual display terminals can reduce the incidence and morbidity associated with this disease. So it can improve the quality of life of workers